Building Cyber - Resilient Smart Cities: Leveraging AI and Big Data for Urban Security - Rachapudi, Sandeep (Journal of Research in Science and Engineering, 2025)
The urgent need to make smart cities resistant to cyber attacks has reached a crucial stage since city infrastructure now uses digital technology. Smart cities operate better through linked networks that use Internet of Things devices as well as bring together artificial intelligence and big data to keep cities secure at all times. Urban infrastructure faces advanced cyber dangers because of its digital transformation especially ransomware attacks, data hackings, and service disruptions The research identifies main cybersecurity difficulties in securing connected networks together with their weak legal standards, data privacy issues, and mixing old systems with new technology. The research paper features AI security methods that help with detecting intrusions and spotting unusual activities with machine learning and improves security through digital twin optimization. This text explains how big data analytics works with cyber situational awareness and making decisions. The study offers best practices and recommends top - level business decisions and security rules. It shows what urban cybersecurity needs to succeed over time.